2010
DOI: 10.28945/1172
|View full text |Cite
|
Sign up to set email alerts
|

Developing Web-Based Learning Resources in School Education: A User-Centered Approach

Abstract: Web-based learning resources (WBLRs) are potentially powerful tools for enhancing teaching and learning processes in school education. They can provide teachers and learners with a wide range of new and exciting experiences that are not possible in a traditional classroom. However, WBLRs are still the domain of technical and software experts rather than teachers and learners. As a result, much of the development of WBLRs is carried out without a true understanding of issues pertinent to learning and pedagogy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 28 publications
1
29
0
4
Order By: Relevance
“…Majority of WBLRs studies on user mathematical performance, self-efficacy, attitudes and acceptance have mainly reported of positive benefits of WBLRs with some few contextual constraints (Guzeller & Akin, 2012;Beki & Guveli, 2008;Kong & Kwok, 2005). As compared with the traditional resources, Hadjerrouit (2010b) indicates that WBLR serves as an added value because the resources promote a new, exciting, active, self-reflected and collaborative learning environment. Following a structured observations of two groups of students who were learning fractions, Kong and Kwok (2005) concluded that the group who used the web material performed better than their colleagues in the control group.…”
Section: Web-based Learning Resourcesmentioning
confidence: 99%
See 4 more Smart Citations
“…Majority of WBLRs studies on user mathematical performance, self-efficacy, attitudes and acceptance have mainly reported of positive benefits of WBLRs with some few contextual constraints (Guzeller & Akin, 2012;Beki & Guveli, 2008;Kong & Kwok, 2005). As compared with the traditional resources, Hadjerrouit (2010b) indicates that WBLR serves as an added value because the resources promote a new, exciting, active, self-reflected and collaborative learning environment. Following a structured observations of two groups of students who were learning fractions, Kong and Kwok (2005) concluded that the group who used the web material performed better than their colleagues in the control group.…”
Section: Web-based Learning Resourcesmentioning
confidence: 99%
“…In recent times, researchers (Akpinar & Simsek, 2007;Hadjerrouit, 2010b) have found a mismatch between existing WBLRs and what teachers, educators and learners need for effective teaching and learning. While the majority of WBLRs are posted online, Hadjerrouit (2010b) emphasized that they do not conform to the instructional goals, philosophical beliefs and intentions of many mathematics teachers.…”
Section: Pedagogical Usability Of Wblrsmentioning
confidence: 99%
See 3 more Smart Citations